1981
DOI: 10.1038/bjc.1981.60
|View full text |Cite
|
Sign up to set email alerts
|

Some mechanisms of local bone destruction by squamous carcinomas of the head and neck

Abstract: Summary.-An in vitro osteolysis assay with 45Ca-labelled mouse calvaria has been used to investigate mechanisms of direct bone invasion by squamous carcinomas of the head and neck. Short-term (3-day) organ cultures of 8 fresh squamous carcinomas showed varying degrees of in vitro bone-resorbing activity which was blocked by indomethacin, an inhibitor of prostaglandin synthesis. Supernatant media from 6 established cell lines also induced bone resorption in vitro and evoked an osteoclastic response in the cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Detailed clinicopathological studies of the patterns of spread of squamous carcinomas of the head and neck into perineural spaces, bone and cartilage, and to regional lymph nodes, have been reported Carter & Pittam, 1980;Tanner et al, 1980); current investigations are concerned with some of the underlying mechanisms, with particular respect to tumourassociated destruction of soft tissues and bone (Tsao et al, 1981). The information that can be obtained from examining fresh tumours is somewhat limited, and access to a number of continuous cell lines derived from squamous carcinomas of the head and neck would considerably facilitate investigations of the behaviour and properties of these tumours.…”
mentioning
confidence: 99%
“…Detailed clinicopathological studies of the patterns of spread of squamous carcinomas of the head and neck into perineural spaces, bone and cartilage, and to regional lymph nodes, have been reported Carter & Pittam, 1980;Tanner et al, 1980); current investigations are concerned with some of the underlying mechanisms, with particular respect to tumourassociated destruction of soft tissues and bone (Tsao et al, 1981). The information that can be obtained from examining fresh tumours is somewhat limited, and access to a number of continuous cell lines derived from squamous carcinomas of the head and neck would considerably facilitate investigations of the behaviour and properties of these tumours.…”
mentioning
confidence: 99%
“…There is much evidence that prostaglandins are synthesised by human carcinomas (Bennett et al, 1975;Dowsett et al, 1976;Tsao et al, 1981Tsao et al, , 1983 and, in view of their potent bone resorbing activity, notably PGE2 (Klein & Raisz, 1970), they have been considered prime candidates as osteolytic mediators. The experiments reported by Tsao et al (1983) showed that although explanted tumour fragments synthesised amounts of PGE2 enough to account for the majority of bone resorption in vitro, the carcinoma cell lines synthesised little prostaglandins but significant prostaglandinindependent osteolytic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The cell lines were established as described by Tsao et al (1981). Two of the squamous carcinoma cell lines (HNI1 and 15) were derived from the floor of the mouth and the third (HN12) from the hypopharynx.…”
Section: Tumour Cellsmentioning
confidence: 99%
See 2 more Smart Citations